Dual rapid lateral flow immunoassay fingerstick wholeblood testing for syphilis and HIV infections is acceptable and accurate, Port-au-Prince, Haiti. Issue 1 (December 2016) - Bristow, Claire; Severe, Linda; Pape, Jean; Javanbakht, Marjan; Lee, Sung-Jae; Comulada, Warren; Klausner, Jeffrey
Abstract Background Dual rapid tests for HIV and syphilis infections allow for detection of HIV infection and syphilis at the point-of-care. Those tests have been evaluated in laboratory settings and show excellent performance but have not been evaluated in the field. We evaluated the field performance of the SD BIOLINE HIV/Syphilis Duo test in Port-au-Prince, Haiti using whole blood fingerprick specimens. Methods GHESKIO (Haitian Study Group for Kaposi's Sarcoma and Opportunistic Infections) clinic attendees 18 years of age or older were invited to participate. Venipuncture blood specimens were used for reference testing with standard commercially available tests for HIV and syphilis in Haiti. The sensitivity and specificity of the Duo test compared to the reference standard were calculated. The exact binomial method was used to determine 95 % confidence intervals (CI). Results Of 298 study participants, 237 (79.5 %) were female, of which 49 (20.7 %) were pregnant. For the HIV test component, the sensitivity and specificity were 99.2 % (95 % CI: 95.8 %, 100 %) and 97.0 % (95 % CI: 93.2 %, 99.0 %), respectively; and for the syphilis component were 96.5 % (95 % CI: 91.2 %, 99.0 %) and 90.8 % (95 % CI: 85.7 %, 94.6 %), respectively. In pregnant women, the sensitivity and specificity of the HIV test component were 93.3 % (95 % CI: 68.0 %, 99.8 %) and 94.1 % (95 % CI: 80.3 %, 99.3 %), respectively; and for the syphilis component were 100 % (95 % CI:81.5 %, 100 %) and 96.8 % (95 % CI:83.3 %, 99.9 %), respectively. Conclusion The Standard Diagnostics BIOLINE HIV/Syphilis Duo dual test performed well in a field setting in Haiti and should be considered for wider use.